2020
DOI: 10.1177/1010539520961715
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Impact of Depression on Cognitive Decline Among Korean Older Adults

Abstract: This study aimed to investigate whether (1) depression is associated with cognitive decline in Korean older adults and (2) the relationship between depression and cognitive function varies by gender. Using Korean Longitudinal Study of Aging data of 2006 to 2014, we studied 1787 adults aged 65 years or older who had normal cognitive function at baseline. This study examined the effects of depression on cognitive decline by using an interaction term of baseline depression and time, and compared relationships by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In the decision tree analysis in the present status, age, which had the greatest impact on cognitive impairment, served as the first layer of this model. Cognitive impairment rates were found to gradually rise with age, in line with prior data from other studies conducted in China and abroad (13,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 88%
“…In the decision tree analysis in the present status, age, which had the greatest impact on cognitive impairment, served as the first layer of this model. Cognitive impairment rates were found to gradually rise with age, in line with prior data from other studies conducted in China and abroad (13,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 88%
“…One possible reason is that the number of older adults participating in formal activities in our sample was much smaller than those participating in informal activities, suggesting potential insu cient power for detecting the interaction effect. Additionally, the cognitive functioning of older adults was in uenced by a bunch of factors, including demographic factors, mental health conditions, and so on [8, 9,10,11,12,13,14,22]. A nonsigni cant interaction effect might be a result of the highly complex interrelationships among these factors.…”
Section: Discussionmentioning
confidence: 99%
“…We controlled for variables that have been shown to affect cognition in addition to depressive symptoms and social participation, including age, gender, education level, marital status, and location of residential address [9,10,11,12,13,14].…”
Section: Control Variablesmentioning
confidence: 99%
“…Moreover, impairment in cognitive ability carries risks for severe loss of cognitive functioning such as dementia and Alzheimer's disease [6,7,8]. Studies have shown that demographic factors contributing to cognitive functioning include gender, age, education, living style, and many other aspects [8,9,10,11,12,13,14]. Supported by previous studies, Zhang and colleagues [9] found that higher odds for cognitive impairment is significantly associated with female, older age, lower education level, living alone with no spousal support, less income, worse psychological well-being, less fresh fruit and vegetable intake, lower social engagement, and more activities of daily living limitations [15,16,17].…”
Section: Introductionmentioning
confidence: 99%